2022
DOI: 10.3390/ph15060730
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Pharmaceutical Properties between Amorphous Drugs Loaded-Mesoporous Silica and Pure Amorphous Drugs Prepared by Solvent Evaporation

Abstract: The formulation of poorly water-soluble drugs is one of the main challenges in the pharmaceutical industry, especially in the development of oral dosage forms. Meanwhile, there is an increase in the number of poorly soluble drugs that have been discovered as new chemical entities. It was also reported that the physical transformation of a drug from a crystalline form into an amorphous state could be used to increase its solubility. Therefore, this study aims to evaluate the pharmaceutical properties of amorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…This phenomenon occurred because some of the AM was recrystallized in the bulk medium, while some was also dissolved gradually. This result was similar to our previous study in which the formation of agglomeration by the drugs decreased the surface area, leading to low wettability and dissolution rate of amorphous drugs [ 39 ]. Therefore, the concentration did not significantly change in dissolution medium for 150 min.…”
Section: Discussionsupporting
confidence: 92%
“…This phenomenon occurred because some of the AM was recrystallized in the bulk medium, while some was also dissolved gradually. This result was similar to our previous study in which the formation of agglomeration by the drugs decreased the surface area, leading to low wettability and dissolution rate of amorphous drugs [ 39 ]. Therefore, the concentration did not significantly change in dissolution medium for 150 min.…”
Section: Discussionsupporting
confidence: 92%
“…Some complexes also formed when the solvent evaporated but were unstable in the long term due to changes or increase in temperature. 21 , 25 , 29 , 30 When complexes are unstable, they can break down or separate back into their original components over time.
Figure 4 Molecular Motion of the Complex System During Molecular Dynamics Simulations using Solvent Evaporation Methods.
…”
Section: Resultsmentioning
confidence: 99%
“…Some complexes also formed when the solvent evaporated but were unstable in the long term due to changes or increase in temperature. 21,25,29,30 When complexes are unstable, they can break down or separate back into their original components over time.…”
Section: Molecular Simulating Motions Of Rtv and Plxmentioning
confidence: 99%
See 1 more Smart Citation
“…This showed that the RTV amorphous was successfully formed by the solvent evaporation method in the RTV alone or after being incorporated into MSNs. 112 Although the PXRD did not detect the presence of an amorphous form, it was discovered that the absence of crystallinity in the samples could not be used to confirm the amorphization of drug by spotting the halo pattern in the diffractogram. 113 DSC Measurement DSC is used to characterize the physical state and location of drug within MSNs by observing their glass transition temperature of melting point.…”
Section: Characterization Of Ggfa Drug Loaded Msns Powder X-ray Diffr...mentioning
confidence: 99%